Serum with phospholipase A2 receptor autoantibodies interferes with podocyte adhesion to collagen - Skoberne, Andrej; Behnert, Astrid; Teng, Beina; Fritzler, Marvin J.; Schiffer, Lena; Pajek, Jernej; Lindic, Jelka; Haller, Hermann; Schiffer, Mario (European Journal of Clinical Investigation, 2014)
Background: The majority of sera from patients with primary membranous nephropathy have autoantibodies against the M-type phospholipase A2 receptor (PLA2R) which is expressed on human podocytes. The rabbit variant of PLA2R attaches to collagen type IV via the fibronectin type II domain, which is also present in the human variant of PLA2R. Design: To assess whether the human PLA2R variant is also involved in attachment to collagen type IV, we conducted a cell adhesion assay on a collagen-coated surface using PLA2R-transfected and mock-transfected human embryonic kidney (HEK) cells. To test the hypothesis that sera from patients containing anti-PLA2R antibodies interfere with the adhesion of podocytes to collagen, we performed cell adhesion assays on a collagen type IV-coated surface using positive and negative serum samples from patients and cultured human podocytes in vitro expressing PLA2R. Results: The HEK cell adhesion assay confirmed an enhanced attachment of PLA2R-transfected cells to collagen type IV. We confirmed diminished podocyte adhesion in the presence of serum with anti-PLA2R antibodies. The concentration of anti-PLA2R antibodies correlated with proteinuria and to the degree of diminished adhesion of podocytes. Conclusions: We demonstrated that serum of patients containing autoantibodies directed to PLA2R interferes with the ability of podocytes to attach to collagen type IV in vitro, providing evidence of a serum soluble pathogenic factor interfering with podocyte adhesion in membranous nephropathy. © 2014 Stichting European Society for Clinical Investigation Journal Foundation.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Cell adhesion; Collagen IV; PLA2R antibodies; Podocyte; Primary membranous nephropathy